Behavior of Reinforced Concrete Beams using Wire Rope as Internal Shear Reinforcement - Colyvas, G. M.; Malecot, Y.; Sieffert, Y.; Aboudha, S.; Kanali, C. (Engineering, Technology & Applied Science Research, 2020)
Wire ropes as internal shear reinforcements could are an economic alternative to conventional stirrups in rectangular concrete beams, mainly due to their attractive advantages such as high flexibility, light weight, and strength. The aim of this study is to enhance the understanding of the shear behavior of concrete beams with continuous spiral-type wire rope as internal shear reinforcement. In order to achieve this objective, an experimental program involving the testing of six beam specimens under four-point load was conducted. Digital image correlation technique was employed to study the crack formation and propagation in the beam specimens. The test results demonstrated that using continuous spiral-type wire rope as shear reinforcement is highly favorable for diagonal crack control. In particular, spiral-type wire rope specimens attained serviceability crack width at a higher load than that of normal stirrup beam specimens.